First record of Theropithecus (Cercopithecidae) from the Republic of Djibouti. Issue 138 (January 2020) - Geraads, Denis; de Bonis, Louis
Abstract: We describe here several specimens of the genus Theropithecus from the southern shore of Lake Assal in the Republic of Djibouti; they are the first record of the genus from this country. We assign them to a derived stage of T. oswaldi . This identification has implications for the age of the informal 'Formation 1' from this area, which should probably be assigned to the Middle Pleistocene. In addition, the presence of T. oswaldi close to the Bab el Mandeb Strait strongly suggests that the species followed this route to India, rather than a more northern one.